H-Ras Oncogene Expression and Angiogenesis in Experimental Liver Cirrhosis - Gülsüm Özlem Elpek; Betül Ünal; Sevgi Bozova (Gastroenterology Research and Practice)
Background. Proto-oncogenes, particularly ras, may not only affect cell proliferation but also contribute to angiogenesis by influencing both proangiogenic and antiangiogenic mediators. The aim of this study was to investigate whether any relationship exists between ras expression and angiogenesis during diethylnitrosamine- (DEN-) induced experimental liver fibrosis. Materials and Methods. Liver cirrhosis was induced in rats by intraperitoneal injections of DEN. The animals were sacrificed 2 weeks after the last administrations and a hepatectomy was performed. Masson’s trichrome staining was used in the evaluation of the extent of liver fibrosis. The vascular density in portal and periportal areas was assessed by determining the count of CD34 labeled vessel sections. For quantitative evaluation of H-ras expression, in each section positive and negative cells were counted. Results. In fibrotic group H-ras expression was higher than that in nonfibrotic group and was more widespread in cirrhotic livers. Friedman’s test showed that there was a significant correlation between H-ras expression and VD (P<0.01). Conclusion. The results of this descriptive study reveal that H-ras expression gradually increases according to the severity of fibrosis and strongly correlates with angiogenesis.